High prevalence of hepatic fibrosis, measured by Elastography, in a Population-based study of Mexican Americans - Watt, Gordon P. (Clin Gastroenterol Hepatol, 2018)
BACKGROUND & AIMS: Hepatic fibrosis is a primary risk factor for cirrhosis and hepatocellular carcinoma, which affect a disproportionate number of Hispanics in the United States. We aimed to determine the prevalence of significant fibrosis, measured by point shear-wave elastography (pSWE), and determine characteristics of hepatic fibrosis and simple steatosis in a population-based study of Mexican American Hispanics in south Texas. METHODS: Liver stiffness was measured by pSWE, performed by 2 separate operators, for 406 participants in the Cameron County Hispanic Cohort from 2015 through 2017. Significant fibrosis (F2–F4) was defined as median stiffness > 1.34 m/s. Steatosis was determined by ultrasound. All participants underwent a clinical examination that included a comprehensive laboratory analysis and standardized interview about their medical and social history. We calculated weighted prevalence of fibrosis and determined clinical and demographic associations with significant fibrosis (with or without steatosis) and simple steatosis with no/minimal fibrosis using multinomial logistic regression. RESULTS: Fifty-nine participants were excluded due to unreliable pSWE findings or inconclusive ultrasound results, for a final analysis of 347 participants. The prevalence of significant fibrosis was 13.8%; most of these participants (37/42, 88.1%) had no evidence of viral hepatitis or heavy drinking. Levels of liver enzymes were associated with fibrosis and simple steatosis. Indicators of metabolic health (insulin resistance, triglycerides, and cholesterol) were significantly associated with simple steatosis. Fibrosis, but not simple steatosis, was significantly associated with of antibodies against HCV in plasma (odds ratio, 18.9; P=.0138) and non-significantly associated with reduced platelet count (odds ratio, 0.8 per 50×10(3)/μL; 95% CI, 0.5–1.1). Multivariable analyses, as well as sensitivity analyses removing F4 fibrosis and viral or alcoholic etiologies, confirmed our results. CONCLUSION: We estimated the prevalence of fibrosis in a large population of Mexican American Hispanics using pSWE measurements. We found Mexican American Hispanics to have a higher prevalence of fibrosis compared to European and Asian populations, primarily attributable to metabolic disease.